2022
DOI: 10.1111/cdep.12440
|View full text |Cite
|
Sign up to set email alerts
|

Promoting racial literacy in early childhood: Storybooks and conversations with young black children

Abstract: Racial literacy as defined by Stevenson (2014) is an important cultural resistance strategy (e.g., positive coping strategy) for Black children and youth because it gives them the skills needed to survive in a racist society. Stevenson’s work, along with the work of several of his colleagues, focuses on adolescents and those in middle childhood, yet it has inspired us to postulate how racial literacy might be fostered in young children (ages 3–8). In this article, we propose a theoretical model for how racial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Read alouds can serve an important role in allowing children to engage about their identities, experiences, and the world around them (Curenton et al, 2022; Husband, 2019; Long and Gove, 2003). Literature circles, which consist of read alouds, in early and elementary classrooms are an important pedagogical tool for teaching young children print concepts, vocabulary, increase their motivation and interests in reading, and strengthening their reading comprehension (Mol et al, 2009; Penno et al, 2002; Snow et al, 1998).…”
Section: Context and Data Collectionmentioning
confidence: 99%
“…Read alouds can serve an important role in allowing children to engage about their identities, experiences, and the world around them (Curenton et al, 2022; Husband, 2019; Long and Gove, 2003). Literature circles, which consist of read alouds, in early and elementary classrooms are an important pedagogical tool for teaching young children print concepts, vocabulary, increase their motivation and interests in reading, and strengthening their reading comprehension (Mol et al, 2009; Penno et al, 2002; Snow et al, 1998).…”
Section: Context and Data Collectionmentioning
confidence: 99%
“…As race scholars have pointed out, racism definitions shape how anti-racist responses and solutions to racism are framed (Azarmandi, 2022;Lentin, 2004;Müller, 2021). International research within early childhood education has identified the need for racial literacy, anti-racist pedagogies, and critical examinations of power to enhance teachers' understandings (Curenton et al, 2022a(Curenton et al, , 2022bEscayg, 2019). Against the backdrop of the Aotearoa New Zealand Ministry of Education's anti-racism policy direction, this article explores how limited definitions of racism within policy documents in Aotearoa New Zealand result in a limited awareness of exactly how to 'unteach' racism in early childhood education contexts.…”
Section: Introductionmentioning
confidence: 99%